2018
DOI: 10.1093/ajcn/nqy113
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled-feeding trial based on the Dietary Guidelines for Americans on cardiometabolic health indexes

Abstract: The consumption of a DGA dietary pattern for 8 wk without weight loss reduced systolic blood pressure. There were no differences between the DGA and TAD diets in fasting insulin, glucose, indexes of insulin resistance, or fasting lipids. This trial was registered at www.clinicaltrials.gov as NCT02298725.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 48 publications
1
49
0
Order By: Relevance
“…A detailed description of the study design was reported by Krishnan et al [ 39 ]. This report is a secondary analysis based on the women who participated in the primary study examining the effects of whole food diets on cardiometabolic risk factors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of the study design was reported by Krishnan et al [ 39 ]. This report is a secondary analysis based on the women who participated in the primary study examining the effects of whole food diets on cardiometabolic risk factors.…”
Section: Methodsmentioning
confidence: 99%
“…The DGA diet contained more whole grains, low-fat dairy, polyunsaturated fat, vegetables, and fruit, while the TAD included more added sugars, refined grains, and solid fats. A specific nutrient breakdown, sample menus, and key products used to prepare meals were previously published [ 39 ]. The trial was conducted at the Western Human Nutrition Research Center in Davis, CA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This theme is previously noted in the ARIC study 33,34 , as well as other U.S. populations 27 , for associations between healthy eating patterns and various chronic disease outcomes. Additionally, previous controlled feeding trials in individuals without diabetes showed little improvement in fasting markers of glycemic control when adopting a weight-maintenance Mediterranean pattern 7 or other heart healthy eating pattern [33][34][35][36][37] in the absence of body weight reductions >2 kilograms.…”
Section: Discussionmentioning
confidence: 93%